Neuroimaging cerebrovascular biomarkers in Parkinson's disease. Issue 4 (August 2022) - Alves, Mariana; Pita Lobo, Patrícia; Azevedo Kauppila, Linda; Rebordão, Leonor; Cruz, M Manuela; Guerreiro, Carla; Ferro, José M; Ferreira, Joaquim J; Reimão, Sofia
Background and Purpose: The cardiovascular risk in Parkinson's disease (PD) remains uncertain and controversial. Some studies suggest PD patients present an increased risk of cerebrovascular disease. We aimed to study the prevalence of neuroimaging cerebrovascular biomarkers in PD patients compared to controls, using an accurate and complete magnetic resonance (MR) imaging evaluation. Material and Methods: Neuroimaging sub-study within a larger cross-sectional case–control study. An enriched subgroup of PD patients (≤10 years since diagnosis) with at least a moderate cardiovascular mortality risk based on a Systematic COronary Risk Evaluation (SCORE) was compared to community-based controls regarding neuroimaging biomarkers. Patients underwent a high-resolution T1-weighted MR imaging sequence at 3.0 T to visualize neuromelanin. A 3D SWI FFE, sagittal 3D T1-weighted, axial FLAIR and diffusion-weighted image sequences were obtained. Results: The study included 47 patients, 24 with PD and 23 controls. PD patients presented a reduced area and signal intensity of the substantia nigra and locus coeruleus on neuromelanin-sensitive MR. The median SCORE was 5% in both groups. No significant differences regarding white matter hyperintensities (OR 4.84, 95% CI 0.50, 47.06), lacunes (OR 0.43, 95% CI 0.07, 2.63), microbleeds (OR 0.64, 95% CI 0.13, 3.26), or infarcts (0.95, 95% CI 0.12, 7.41) was found. The frequency of these neuroimaging biomarkers was very low in both groups. Conclusion: The present study does not support an increased prevalence of neuroimaging cerebrovascular biomarkers in PD patients.